2016
DOI: 10.1186/s12862-016-0733-x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic modelling in a dynamic evolutionary framework predicts adaptive diversification of bacteria in a long-term evolution experiment

Abstract: BackgroundPredicting adaptive trajectories is a major goal of evolutionary biology and useful for practical applications. Systems biology has enabled the development of genome-scale metabolic models. However, analysing these models via flux balance analysis (FBA) cannot predict many evolutionary outcomes including adaptive diversification, whereby an ancestral lineage diverges to fill multiple niches. Here we combine in silico evolution with FBA and apply this modelling framework, evoFBA, to a long-term evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 74 publications
3
81
0
Order By: Relevance
“…The idea of cellular tradeoffs driving the emergence of metabolic cross‐feeding has recently been evaluated in a combined in silico and experimental evolution study (Großkopf et al ., ). In that study, the authors have incorporated tradeoffs in a stoichiometric metabolic model of Escherichia coli by imposing global constraints on the total uptake rates.…”
Section: Microbial Cooperations Based On Metabolic Interactionsmentioning
confidence: 97%
See 2 more Smart Citations
“…The idea of cellular tradeoffs driving the emergence of metabolic cross‐feeding has recently been evaluated in a combined in silico and experimental evolution study (Großkopf et al ., ). In that study, the authors have incorporated tradeoffs in a stoichiometric metabolic model of Escherichia coli by imposing global constraints on the total uptake rates.…”
Section: Microbial Cooperations Based On Metabolic Interactionsmentioning
confidence: 97%
“…C). These two models have distinct uptake fluxes suggestive of a cross‐feeding interaction; one model had increased glucose uptake and acetate excretion rate and the other had increased acetate uptake rate (Großkopf et al ., ). Further experimental analyses revealed that the two models show metabolic flux patterns that qualitatively match experimentally observed genotypes in one lineage of the long‐term experiments, indicating that this approach might provide useful insights into how ecological and evolutionary dynamics can shape metabolic systems.…”
Section: Microbial Cooperations Based On Metabolic Interactionsmentioning
confidence: 97%
See 1 more Smart Citation
“…Diversification events within populations often entail cross-feeding interactions [12,13,[15][16][17][18], where species emerge that grow on metabolic by-products. These cross-feeding interactions are increasingly well understood with the help of metabolic modeling and digital evolution [19,20]. A recent metagenomic study has revealed even more coexisting lineages in the LTEE than were previously reported [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, ever larger datasets are being generated using high-throughput phenotyping and whole genome sequencing, and computational and modeling approaches are increasingly successful at combining such data across multiple organizational levels. For example, a recent model that integrated flux balance analysis with eco-evolutionary dynamics correctly predicted the evolution of cross-feeding in the E. coli long-term evolution experiment (Grosskopf et al 2016).…”
Section: Genetics Of Adaptationmentioning
confidence: 98%